NC

Tìm GTLN của:

A= 4 - x^2+2x

B= -x^2+3x+6

NP
15 tháng 9 2018 lúc 15:18

\(A=4-x^2+2x=5-x^2+2x-1=5-\left(x^2-2x+1\right)\)

\(=5-\left(x-1\right)^2\le5\)nên GTLN của A là 5 đạt được khi x=1

\(B=-x^2+3x+6=-x^2+2.\frac{3}{2}x-\frac{9}{4}+\frac{33}{4}=-\left(x^2-2.\frac{3}{2}.x+\frac{9}{4}\right)+\frac{33}{4}\)

\(=-\left(x-\frac{3}{2}\right)^2+\frac{33}{4}\le\frac{33}{4}\) nên GTLN của B là \(\frac{33}{4}\) đạt được khi \(x=\frac{3}{2}\)

Bình luận (0)

Các câu hỏi tương tự
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
VC
Xem chi tiết
NH
Xem chi tiết
TN
Xem chi tiết
TK
Xem chi tiết
HM
Xem chi tiết
SH
Xem chi tiết